Expression of a rice chitinase gene in transgenic banana (‘Gros Michel’, AAA genome group) confers resistance to black leaf streak disease - Kova´cs, Gabriella; Sa´gi, La´szlo´; Jacon, Ge´raldine; Arinaitwe, Geofrey; Busogoro, Jean-Pierre; Thiry, Els; Strosse, Hannelore; Swennen, Rony; Remy, Serge (Transgenic research, 2013)
Transgenic banana (Musa acuminata ‘Gros Michel’) integrating either of two rice chitinase genes was generated and its resistance to Black Leaf Streak disease caused by the fungus Mycosphaerella fijiensis was tested using a leaf disk bioassay. PCR screening indicated the presence of the hpt selectable marker gene in more than 90 % of the lines tested, whereas more than three quarters of the lines contained the linked rice chitinase gene resulting in a co-transformation frequency of at least 71.4 %. Further, a unique stable integration of the transgenes in each line revealed some false negative PCR results and the expected co-transformation frequency of 100 %. Gabriella Kova´cs, La´szlo´ Sa´gi contributed equally to this work.
Keywords: Black leaf streak disease Leaf disk assay Musa spp. Mycosphaerella fijiensis Transgenic banana